Fractal Analysis of Skeletal Muscle Tissue of Rats Subjected to Stretch Injury - Ozaki, Guilherme [UNESP]; Trindade Camargo, Regina Celi [UNESP]; Koike, Tatiana Emy [UNESP]; Garcia, Thiago Alves [UNESP]; Castoldi, Robson Chacon [UNESP]; Silva Camargo Filho, Jose Carlos [UNESP] (Soc Chilena Anatomia, 2015)
The aim of this study was to analyze changes in the skeletal muscle tissue of rats after muscle stretch injury using fractal analysis. Nineteen rats were divided into three groups, Control (n=5) (C), Lesion two days (n=7) (L2), and Lesion seven days (n=7) (L7). Histological slides of the gastrocnemius muscle of the animals were prepared and stained with Hematoxylin and eosin for analysis of the inflammatory process, and picrosirius for the demonstration of collagen. The stained slides were subsequently analyzed using Fractal Dimension (FD). The results showed high FD values of the inflammatory process in the experimental groups L2 and L7 in relation to C (p=0.000). The analysis of collagen in the picrosirius stained slides showed high FD in the L2 group compared to the L7 (p=0.0001), with no statistically significant difference among other groups. In summary, the present study demonstrated that fractal analysis was able to identify changes in the inflammatory process in injured skeletal muscle tissue.
Keywords: Fractal analysis; Skeletal muscle injury; Collagen; Inflammation; Pathology